Long‐term efficacy and safety of ertugliflozin in patients with type 2 diabetes mellitus inadequately controlled with metformin monotherapy: 104‐week VERTIS MET trial. Issue 4 (14th February 2019) - Gallo, Silvina; Charbonnel, Bernard; Goldman, Allison; Shi, Harry; Huyck, Susan; Darekar, Amanda; Lauring, Brett; Terra, Steven G.
Abstract : Aim: To evaluate the long‐term efficacy and safety of ertugliflozin in adults with type 2 diabetes mellitus inadequately controlled on metformin. Materials and Methods: A 104‐week Phase III, randomized double‐blind study with a 26‐week placebo‐controlled period (Phase A) and a 78‐week period (Phase B) where blinded glimepiride was added to non‐rescued placebo participants with fasting fingerstick glucose ≥6.1 mmol/L. Results through week 104 are reported. Results: Mean (standard error) change in HbA1c from baseline was −0.7% (0.07) and −1.0% (0.07) at week 52; −0.6% (0.08) and −0.9% (0.08) at week 104 for ertugliflozin 5 and 15 mg. At week 52, 34.8% and 36.6% participants had HbA1c <7.0%, and 24.6% and 33.7% at week 104, for ertugliflozin 5 and 15 mg. Ertugliflozin reduced fasting plasma glucose (FPG), body weight and systolic blood pressure (SBP) from baseline through week 104. The incidence of female genital mycotic infections (GMIs) was higher with ertugliflozin, and symptomatic hypoglycaemia was lower for ertugliflozin versus placebo/glimepiride. Minimal bone mineral density (BMD) changes were observed, similar to placebo/glimepiride, except at total hip where reduction in BMD was greater with ertugliflozin 15 mg versus placebo/glimepiride: difference in least squares means (95% CI) –0.50% (−0.95, −0.04) at week 52 and −0.84% (−1.44, −0.24) at week 104. Conclusions: Ertugliflozin maintained improvements from baseline in HbA1c, FPG, body weight and SBP through week 104. Ertugliflozin was well tolerated, with non‐clinically relevant changes in BMD. Compared with placebo/glimepiride, ertugliflozin increased female GMIs, but reduced the incidence of symptomatic hypoglycaemia. ClinicalTrials.gov Identifier: NCT02033889.